Students’ satisfaction and learning experiences at higher agricultural education institutions in Saudi Arabia: an empirical inquest - Alotaibi, Bader Alhafi; Muddassir, Muhammad; Abbas, Azhar; Nayak, Roshan K.; Azeem, Muhammad Imran (Frontiers in Education, 2024)
This study aims to explore various factors that affect students' satisfaction regarding postgraduate agricultural programs and the likelihood of recommending such programs to others. Methods: Data were collected using structured paper-based questionnaires from a random sample of 127 students who were undertaking master and doctoral programs in eight different disciplines within agricultural sciences at King Saud University.The findings showed that majority of the students expressed high academic learning experiences and were satisfied with their program of study. Multiple regression analysis revealed that students' academic learning experience, faculty support, and the rationale for attending the university had significant positive influence on their satisfaction with the enrolled programs. Moreover, the students' satisfaction and faculty support also showed significant positive correlation with their likelihood to recommend agricultural programs to others. Suggestions: In order to further enhance the impact of agricultural programs, we suggest improvements in the university curriculum as well as faculty services to make current agricultural programs up-to-date and relevant to meet the kingdom's national agricultural and human resource development goals. There should be a particular focus on enhancing students' research and written communication skills as postgraduate agricultural programs entail a significant component of these highly essential skills.